Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Durability of the moderate-to-heavy intensity transition can be predicted using readily available markers of physiological decoupling - Jeffrey A. Rothschild; Gabriele Gallo; Kate Hamilton; Julian D. Stevenson; Harrison Dudley-Rode; Thanchanok Charoensap; Daniel J. Plews; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2025)
Purpose To assess relationships between heart rate (HR), ventilation (̇ $$\dot V$$ V ˙ E ), and respiratory frequency (F R ) decoupling and durability of the first ventilatory threshold (VT 1 ), and the strength of practical models to predict power output at VT 1 during prolonged exercise. Methods Durability of VT 1 was assessed via measurements of power output at VT 1 before and after ~ 2.5-h of initially moderate-intensity cycling in 51 trained cyclists, as part of four studies published elsewhere. In 12 of those participants, power output at VT 1 was assessed every hour until task failure. For every assessment of power output at VT 1 , HR, F R , and $$\dot V$$ V ˙ ̇ E was measured at fixed power outputs, and thus decoupling of these variables with power output was determined. Bivariate repeated-measures correlations (r rm ) between decoupling and durability of VT 1 were assessed. Multivariable models were created to predict power output at VT 1 during prolonged exercise using generalised estimating equations. Results Negative correlations were observed between exercise-induced change in power output at VT 1 and HR (r rm = −0.76, P < 0.001) and F R (r rm = −0.40, P = 0.013) decoupling, but not $$\dot V$$ V ˙ ̇ E decoupling (r rm = −0.25, P = 0.136). The final prediction model, containing baseline VT 1 and peak oxygen uptake, F R decoupling, and an interaction between HR decoupling and exercise duration, effectively predicted real-time VT 1 (mean absolute error, ~ 7.2 W; R 2 , 0.95). Conclusion HR and/or F R decoupling during controlled training sessions may be a practically useful durability assessment. Our prediction models may be an effective means of improving within-session intensity regulation and training load monitoring.

Modelling temperature variations in Birmingham, UK at the neighbourhood scale: Using ADMS-Urban climate model - Jian Zhong; Yanzhi Lu; Jenny Stocker; Victoria Hamilton; Kate Johnson (Sustainable Cities and Society, 2025)

Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Kate Hamilton; Andrew E. Kilding; Daniel J. Plews; Mathew J. Mildenhall; Mark Waldron; Thanchanok Charoensap; Tobias H. Cox; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed ‘durability’. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability. Methods On separate days, 13 well-trained cyclists and triathletes (V̇O 2 peak, 57.3 ± 4.8 mL kg −1 min −1 ; training volume, 12 ± 2.1 h week −1 ) undertook an incremental test and 5-min time trial (TT) to determine power output at the first ventilatory threshold (VT 1 ) and severe-intensity performance, with and without 150-min of prior moderate-intensity cycling. A single resting vastus lateralis microbiopsy was obtained. Results Prolonged exercise reduced power output at VT 1 (211 ± 40 vs. 198 ± 39 W, ∆ -13 ± 16 W, ∆ -6 ± 7%, P = 0.013) and 5-min TT performance (333 ± 75 vs. 302 ± 63 W, ∆ -31 ± 41 W, ∆ -9 ± 10%, P = 0.017). The reduction in 5-min TT performance was significantly associated with durability of VT 1 (r s = 0.719, P = 0.007). Durability of VT 1 was not related to vastus lateralis carnosine content, citrate synthase activity, or complex I activity ( P > 0.05). Conclusion These data provide the first direct support that durability of the moderate-to-heavy-intensity transition is an important performance parameter, as more durable athletes exhibited smaller reductions in 5-min TT performance following prolonged exercise. We did not find relationships between durability and vastus lateralis carnosine content, citrate synthase activity, or complex I activity.

Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Establishment and characterization of a platinum- and paclitaxel-resistant high grade serous ovarian carcinoma cell line - Pang-Ning Teng; Nicholas W. Bateman; Guisong Wang; Tracy Litzi; Brian E. Blanton; Brian L. Hood; Kelly A. Conrads; Wei Ao; Kate E. Oliver; Kathleen M. Darcy; William P. McGuire; Keren Paz; et al. (Human Cell, 2017)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Neuromuscular synapses on the dactyl opener muscle of the lobster Homarus americanus - Jonna Hamilton; Richard M. Dillaman; Mary Kate Worden (Cell and Tissue Research, 2006)

Forest carbon balance under elevated CO2 - Jason G. Hamilton; Evan H. DeLucia; Kate George; Shawna L. Naidu; Adrien C. Finzi; William H. Schlesinger (Oecologia, 2002)